Does Audit Software Adoption Matter? Evidence from Local CPA Firms in Indonesia - Judith Sinaga (CogITo Smart Journal, 2024)
The integration of technology in the audit practice is widely used nowadays.  IT-based audits are applied since most of the accounting transactions are done computerized.  This paper aims to assess the adoption of audit software by local CPA Firms in Jakarta and Medan, Indonesia. This research used the descriptive method with the quantitative approach. The research was conducted at five local CPA firms in Jakarta and Medan, with a research sample of 63 auditors.  Data collections were done through questionnaires. Descriptive statistics, correlation, and regression were used to analyze data. The results of this study showed that perceived benefit and company readiness have positive and significant effects on the adoption of audit software.  Adoption risk has a negative and significant effect on the adoption of audit software, and external pressure has no significant effect on the adoption of audit software. This research provides added value to all local CPA firms and makes audits more efficient and effective.  It encourages all local firms to conduct the audit in a more advanced method through the use of audit software. This research corroborates the previous research in a different context (types of business and place).  It focused more on a partnership type of business.